Thermal behavior of magnetized blood–CMS hybrid nanofluid with SWCNT and MWCNT suspensions: Prabhakar fractional model - Urwa Shehbaz; Sami Ullah Khan; Aboulbaba Eladeb; Nermeen Abdullah; Chemseddine Maatki; Lioua Kolsi (Case Studies in Thermal Engineering)
This analysis investigates natural convective (mixed convection) hybrid nanofluid (HNF) flow within a channel by using advanced definitions of fractional operators. The hybrid nanofluid consists of single-walled and multi-walled carbon nanotubes (SWCNTs-MWCNTs) dispersed in blood and carboxymethyl starch (CMS) base fluids. The fractional computations are performed with help of Prabhakar fractional model. The Laplace transformed is implemented to governing equations involving the Prabhakar operator, the Stehfest numerical inversion algorithm is implemented to retrieve the time-domain computations. Such approach ensures the accurate implementation of Laplace transport to evaluate the effective thermal and flow fields. A detailed comparative analysis is conducted to ensure the validity of fractional model. The findings indicate that blood-based hybrid nanofluids exhibit a more pronounced influence on thermal and momentum transport compared to CMS-based nanofluids, making them more effective for biomedical and industrial heat transfer applications.